Comparative study on the impact of through-space charge transfer over the electroluminescence performance of delayed fluorescence molecules. Issue 41 (11th October 2021) - Yu, Maoxing; Zhu, Xiangyu; Zeng, Jiajie; Liu, Hao; Huang, Ruishan; Zhuang, Zeyan; Shen, Pingchuan; Zhao, Zujin; Tang, Ben Zhong
Abstract : A comparative study on the impacts of through-space charge transfer and through-bond charge transfer on the photoluminescence and electroluminescence properties of the delayed fluorescence molecules is conducted. Abstract : Through-space charge transfer (TSCT) is adopted in the design of thermally activated delayed fluorescence (TADF) emitters owing to the facile separation of frontier orbitals. However, the advantages of TSCT in the creation of TADF emitters has not been fully resolved. To address this issue, we design and synthesize a series of V-shaped molecules with TSCT and linear molecules with through-bond charge transfer (TBCT), consisting of a 1, 3, 5-triazine acceptor, a phenoxazine or phenothiazine donor, and an o - or p -terphenyl bridge. A comparative study is conducted to demonstrate their differences in photoluminescence (PL) and electroluminescence (EL) properties. Both kinds of molecules have apparently separated frontier orbitals and prominent aggregation-induced delayed fluorescence properties. Owing to the through-space edge-to-face alignment, the V-shaped molecules with TSCT exhibit higher solid-state PL quantum yields and faster reverse intersystem crossing processes than the linear molecules with TBCT. The V-shaped molecules hold better EL performances with higher EL efficiencies and smaller efficiency roll-offs than linear molecules, regardless of whether they are in nondoped or doped organic light-emitting diodes (OLEDs). These results indicate that TSCT could be a good choice for the creation of TADF emitters, particularly for those with long conjugation molecular backbones.